Lexicography in-your-face: The active semantics of Pastaza Quichua ideophones. (3rd April 2017) - Nuckolls, Janis B.; Swanson, Tod D.; Shelton, Diana; Rice, Alexander; Hatton, Sarah
Abstract: We argue that a multimodal approach to defining a depictive class of words called 'ideophones' by linguists is essential for grasping their meanings. Our argument for this approach is based on the formal properties of Pastaza Quichua ideophones, which set them apart from the non-ideophonic lexicon, and on the cultural assumptions brought by speakers to their use. We analyze deficiencies in past attempts to define this language's ideophones, which have used only audio data. We offer, instead, an audiovisual corpus which we call an 'antidictionary', because it defines words not with other words, but with clips featuring actual contexts of use. The major discovery revealed by studying these clips is that ideophones' meanings can be clarified by means of a distinction found in modality and American Sign Language studies. This distinction between speaker-internal and speaker-external perspective is evident in the intonational and gestural details of ideophones' use. Résumé: Nous soutenons que pour définir une classe de mots descriptifs appelés « idéophones », il est essentiel d'adopter une approche multimodale, si l'on veut saisir toutes les nuances de leur signification. Notre argument en faveur de cette approche se base d'une part sur les propriétés formelles des idéophones Pastaza Quichua, propriétés qui les distinguent du lexique non idéophonique, et d'autre part sur les hypothèses culturelles que les locuteurs contribuent à leur utilisation. Nous analysons les lacunes des efforts antérieurs cherchant à définir les idéophones de cette langue, qui n'ont fait appel qu'à des données audio. Nous proposons plutôt un corpus audiovisuel, que nous appelons « anti-dictionnaire » parce qu'il définit des mots non pas à l'aide d'autres mots, mais avec des vidéoclips qui mettent en scène d'authentiques contextes d'utilisation. La principale révélation de ces clips est que les significations des idéophones peuvent être clarifiées à l'aide d'une distinction que l'on trouve dans les études sur la modalité, et sur l'ASL (la langue des signes américaine); cette distinction entre les perspectives interne et externe au locuteur se manifeste dans des détails d'intonation et de gestuelle qui caractérisent l'usage des idéophones.